DETERMINASI NIAT PEMBAYARAN PAJAK ATAS TRANSAKSI E-COMMERCE (STUDI PADA WAJIB PAJAK ORANG PRIBADI DAN BADAN PELAKU E-COMMERCE DI WILAYAH KABUPATEN TEMANGGUNG) - Muhammad Nurakhim (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This study aims to test whether knowledge and understanding of tax regulations, taxpayer awareness and taxpayer environment have an effect on tax payment intentions for E-commerce transactions. The research method uses quantitative descriptive methods and primary data with a questionnaire. This study took a sample of individual taxpayers and the E-commerce Implementing Body in the Temanggung district. Data processing was carried out by classical assumption test and hypothesis test with normality test, multicollinearity test, heteroscedasticity test, T test, F test, and R2. The sampling technique in this study is to use incidental sampling. The collection technique is done by using a link questionnaire in the form of google. The number of questionnaires that were processed was 100 questionnaires. The results showed that the knowledge and understanding of tax regulations and the taxpayer environment had a negative effect on tax payment intentions for E-commerce transactions, while taxpayer awareness had a positive effect on tax payment intentions for E-commerce transactions on individual taxpayers and trading entities. electronic. Keyword: tax payment, e-commerce, knowledge and understanding of tax regulations